Teaching the Central Dogma of Molecular Biology using Jewelry - Jennifer M. DeBruyn (American Society for Microbiology, 2012)
”Cracking the Code” is an activity developed to demonstrate the processes of transcription and translation. This hands-on activity helps students understand the relationship between form (base pairing) and function (information storage and transfer) of nucleic acids. In this activity, students go through the processes of transcription and translation of a DNA molecule to create jewelry; a beaded bracelet or necklace is used as a tactile representation of a chain of amino acids. To determine the correct order of “amino acid” beads, students must first decode a strand of DNA using complementary base pairing rules. The decoding is a two-step process that illustrates transcription (the copying of DNA to RNA) and translation (using tRNAs to match the genetic code to the correct amino acid). This teaches the relationship between structure (base pairs) and function (information storage and transfer) in nucleic acids.